Effectiveness of the 'Girls Active' school-based physical activity programme: A cluster randomised controlled trial - Deirdre M. Harrington; Melanie J. Davies; Danielle H. Bodicoat; Joanna M. Charles; Yogini V. Chudasama; Trish Gorely; Kamlesh Khunti; Tatiana Plekhanova; Alex V. Rowlands; Lauren B. Sherar; Rhiannon Tudor Edwards; Thomas Yates; et al. (BMC, 2018)
Abstract Background Globally, adolescent girls' physical activity (PA) levels are low. The 'Girls Active' secondary school-based programme, developed by the Youth Sport Trust, aims to increase PA in adolescent girls. This paper explores the effectiveness of the 'Girls Active' school-based PA programme. Methods A random sample of girls aged 11-14 from 20 secondary schools (Midlands, UK) participated in a two-arm cluster randomised controlled trial. Ten schools received Girls Active and 10 continued with usual practice. Measurements were taken at baseline, seven- and 14-month follow-up. Primary outcome: wrist-worn accelerometer measured moderate- to vigorous-intensity PA (MVPA). Secondary outcomes: overall PA, light PA, sedentary time, body composition, and psychosocial outcomes. Generalised estimating equations, adjusted for school cluster and potential confounders, were used and A priori subgroup analysis was undertaken. Micro-costing and cost-consequence analyses were conducted using bespoke collection methods on programme delivery information. Outcomes for the cost-consequence analysis were health related quality of life measured by the Child Health Utility-9D and service use. Results Overall, 1752 pupils participated, 1211 (69.1%) provided valid 14-month accelerometer data. No difference in MVPA (mins/day; 95% confidence intervals) was found at 14 months (1.7; -0.8 to 4.3), there was at seven months (2.4; 0.1 to 4.7). Subgroup analyses showed significant intervention effects on 14-month in larger schools (3.9; 1.39 to 6.09) and in White Europeans (3.1; 0.60 to 6.02) and in early maturers (5.1; 1.69 to 8.48) at seven months. The control group did better in smaller schools at 14-months (-4.38; -7.34 to -1.41). Significant group differences were found in 14-month identified motivation (-0.09; -0.18 to -0.01) and at seven months in: overall PA (1.39 mg/day; 0.1 to 2.2), after-school sedentary time (-4.7; -8.9 to -0.6), whole day (5.7; 1.0 to 10.5) and school day (4.5; 0.25 to 8.75) light PA, self-esteem. Small, statistically significant, differences in some psychosocial variables favoured control schools. Micro-costing demonstrated that delivering the programme resulted in a range of time and financial costs at each school. Cost-consequence analysis demonstrated no effect of the programme for health related quality of life or service use. Conclusions Compared with usual practice, 'Girls Active' did not affect 14-month MVPA. Trial registration ISRCTN10688342